2000
DOI: 10.1046/j.1365-3083.2000.00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Immature B Cells in Bone Marrow Express Fas/FasL

Abstract: Negative selection is a process by which autoreactive lymphocytes are eliminated from the developing antigen receptor repertoire. The mechanisms regulating negative selection of immature B lymphocytes in the bone marrow are poorly elucidated. Human bone marrow cells were examined in order to investigate the presence of the members of the Fas (APO-1/CD95) system. Here we demonstrate the expression of Fas in immature B lymphocytes (CD10/CD19+/CD40+/sIg+), and the presence of Fas natural ligand (FasL) in CD19+ bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 29 publications
(34 reference statements)
0
11
0
1
Order By: Relevance
“…However, this idea is now controversial, because several recent reports indicate that activated B cells can express FasL (3,(13)(14)(15)(16)(17). Furthermore, FasL expressed on B cells activated by S. mansoni soluble egg Ags is functional, because it is able to kill a Fas-bearing target cell line (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this idea is now controversial, because several recent reports indicate that activated B cells can express FasL (3,(13)(14)(15)(16)(17). Furthermore, FasL expressed on B cells activated by S. mansoni soluble egg Ags is functional, because it is able to kill a Fas-bearing target cell line (4).…”
Section: Discussionmentioning
confidence: 99%
“…Fasdeficient lpr and FasL-deficient gld mice present generalized lymphoproliferation and produce autoantibodies resembling human systemic lupus erythematosus (12). Recent reports have demonstrated FasL expression on the B cell compartment (3,4,(13)(14)(15)(16)(17), but the functional role of this expression is a matter of controversy. In vivo experiments with mixed gld chimeras suggested that FasL controls the expansion of lymphocytes only when expressed on T cells (18).…”
mentioning
confidence: 99%
“…Significantly, an in vivo role for B cellmediated apoptosis during infection was suggested by the increased CD4 ϩ T cell death following adoptive transfer of SEAstimulated, FasL-bearing B cells. Previous studies have shown that mitogen-activated B cells expressed surface FasL (16) and that FasL expression was detectable on B cells isolated from human tonsil and bone marrow (20,30). Recent studies have demonstrated Epstein-Barr virus-and lectin-inducible FasL expression on B cells (8,34).…”
Section: Discussionmentioning
confidence: 99%
“…Inducible expression of FasL has generally been studied on T lymphocytes following activation by mitogens or through the T cell receptor complex (21). However, several recent reports indicate that activated B cells can express functional FasL (8,16,30,34). Susceptibility to FasL-mediated apoptosis is determined by the expression of the death receptor, Fas (CD95, Apo1), and by the activation state of the target cell (29).…”
Section: Cd4mentioning
confidence: 99%
“…Several other studies have demonstrated the expression of FasL on B cells freshly isolated from human lymphoid organs [40, 68, 87]. In one of these studies, expression of FasL was low in the thymus and most lymph nodes, but was detected in the spleen, tonsil and mucosal-associated lymphoid tissue, primarily on Ig + plasma cells [87].…”
Section: Death Ligand Expression By B Cellsmentioning
confidence: 99%